A Proposed Enhancement Initiative for Employee Engagement, Organizational Resiliency, and Organizational Sustainability: A Case of the Center for Diversity and National Harmony (CDNH) Myanmar: Article Submission - Naing, Nyi Nyi; Preudhikulpradab, Sirichai; Barnes, John Arthur (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
This mixed-method research has three objectives: 1) examine the current condition of employee engagement, organizational resiliency, and organizational sustainability of all employees’ levels and rank the priority needs; 2) explore interviewees’ perceptions of how to enhance employee engagement, organizational resiliency, and sustainability. 3). develop an initial proposal for enhancement initiative, organizational resiliency, and sustainability at CDNH. The instruments employed included: aquestionnaire (N=90) and an in-depth interview (N=10). The target populations comprise all employees, middle-level management, and top-level management, the purposive sampling method. The data analysis treatments include descriptive statistics and PNI Modified for the structured questionnaire and contents analysis for the interview. Findings showed that based on the PNI modified, Employee Engagement (PNI Modified =0.345) was ranked as the priority need for organizational sustainability in the Center for Diversity and National Harmony, Organizational Resilience (PNI Modified = 0.334) was ranked as the second priority need level, the Organization Sustainability (PNI Modified = 0.249) was ranked the third. The recommendations are that the CDNH organization focuses on the three main competencies factors to develop enhancement initiatives for employee engagement, organizational resiliency, and organizational sustainability. Lastly, the data obtained from the questionnaire and open-response questions were analyzed by using descriptive statistics and content analysis. According to the content analysis inter-coding, social harmony, stakeholder engagement, and accountability and transparency had been mentioned among 10 informants that could be improved for employee engagement, organizational resilience, and organization sustainability. Additionally, the key informants believe that team building, creating a good working environment, and staff capacity building are factored in developing these three areas. As there are many levels and employees within the organization at the same time, it might not be unity. Moreover, allocating their workplace without creating or supporting a good working environment was discussed among 10 key informants. Lastly, the informants believe that building staff capacity was considered a critical need for employees according to their tasks and responsibility. For further studies, to identify conducting research focused on stakeholders’ engagement and working conditions, as well as employees’ satisfaction in the Center for Diversity and National Harmony.